Indoor air quality and its relationship with building design, building operation, and occupants' behaviour in Johor public hospital outpatient departments - Ibrahim, Farha (2024)
Poor indoor air quality (IAQ) in healthcare settings may adversely impact occupants' well-being and promote the transmission of infectious respiratory disease. However, evidence on IAQ in hospital outpatient departments (OPDs) and its building and occupant-related factors remains scarce. This study aims to determine the relationship between building design, building operation, and occupants' behaviour with IAQ in Johor public hospital OPDs. A multistage cross-sectional study of six randomly selected Johor public hospital OPDs was conducted. In stage one, IAQ parameters, including temperature, relative humidity (RH), air velocity (AV), carbon dioxide (CO2), total bacterial count (TBC), and total fungal count (TFC) were measured. In stage two, hospital records on building design and operation of selected hospital OPDs were examined. In stage three, an observation form based on the Korsavi and Montazami (2019) validated tool for measuring adaptive behaviours was used to examine occupant density, activities, and operation of building envelopes and appliances. Simple correlation, partial correlation, and linear regression analyses were then performed to examine the relationship of building design, building operation, and occupant behaviour with IAQ parameters. Based on the IAQ parameter measurements (n=384), the study results indicated that the IAQ of selected hospital OPDs complied with established standards, except for temperature, RH, and AV. In terms of building design, ventilation system design was negatively correlated with temperature, RH, AV, CO2, TBC, and TFC, whereas the total number of appliances was positively correlated with AV. Meanwhile, the size of OPD was positively correlated with TBC and TFC. With regards to occupant behaviour, occupant density was positively correlated with temperature, RH, AV, CO2, TBC, and TFC. Meanwhile, based on the observation of selected hospital OPD occupants (n=151), occupants' activities including slow walking and brisk walking were positively correlated with temperature, AV, CO2, TBC, and TFC, whereas occupants' opening of windows and doors was positively correlated with temperature and AV but negatively correlated with CO2, TBC, and TFC. Finally, turning on fans was positively correlated with AV but negatively correlated with TBC, whereas turning on the air conditioner was positively correlated with CO2. On the whole, ventilation system design and occupants’ operation of doors and windows contributed the most to variation in IAQ parameters. The study findings suggest that the IAQ of hospital OPDs are significantly related to building design and occupant behaviour factors, including ventilation system design, number of appliances, OPD size, occupant density, occupant activities, and occupants’ operation of building envelopes and appliances. Consequently, multidisciplinary and multipronged strategies considering these important building and occupant-related determinants are deemed viable for the future control and improvement of hospital IAQ.